CEO turnover in public and private organizations: Analysis of the relevance of different performance horizons - Esteban Lafuente; Miguel Angel García Cestona (Journal of Economics, Finance and Administrative Science, 2021)
Purpose - This paper investigates how past performance changes, prior CEO replacements and changes in the chairperson impact CEO turnover in public and large private businesses. Design/methodology/approach - We analyze 1,679 CEO replacements documented in a sample of 1,493 Spanish public and private firms during 1998-2004 by computing dynamic binary choice models that control for endogeneity in CEO turnovers. Findings - The results reveal that different performance horizons (short- and long-term) explain the dissimilar rate of CEO turnover between public and private firms. Private firms exercise monitoring patience and path dependency characterizes the evaluation of CEOs, while public companies' short-termism leads to higher CEO turnover rates as a reaction to poor short-term economic results, and alternative controls-ownership and changes in the chairperson-improve the monitoring of management. Originality/value - Our results show the importance of controlling for path dependency to examine more accurately top executives' performance. The findings confirm that exposure to market controls affects the functioning of internal controls in evaluating CEOs and shows a short-term performance horizon that could be behind the recent moves of public firms going private or restraining shareholders' power.
Keywords: 330; CEO turnover; Dynamic binary choice models; Path dependency; Private firms; Public firms